Effects of canning temperature and period on the proximate composition of oyster mushrooms (Pleurotus ostreatus) and the functional properties of its brine - Nurul’ain Natasha, Rivoldiantoe; Tan, Cindy Soo Yun; Shanti Faridah, Salleh; Mohd Jamil, Mohamed Mokhtarudin; Jumardi, Roslan; Noorakmar, Ab Wahab (Malaysian Institute of Chemistry, 2025)
Canning is a method for preserving perishable items, including edible mushrooms. However, the high temperatures applied during canning result in nutritional degradation and leaching into the brine. This study measured the proximate composition of oyster mushrooms after canning at three different temperatures (116, 121, and 126 °C) and periods (25, 30, and 35 minutes). Foaming capacity, foaming stability, and emulsion capacity tests were performed to establish the brine’s functional qualities, while the SDS-PAGE technique was used to identify the molecular weight of the proteins. The results demonstrated that the canning temperature and period significantly reduced the protein and fat levels of oyster mushrooms (p < 0.05) by approximately 20.20 % and 50.30 %, respectively. This outcome suggests nutrient denaturation and leaching during the canning process of oyster mushrooms. In contrast, the ash and fibre levels of the mushroom samples increased with canning temperature and period (p < 0.05). The brine of canned mushrooms subjected to > 30 minutes of the canning process exhibited improved foam formation (60 - 83 %) and the greatest stability (p < 0.05). Gel electrophoresis revealed that the proteins in the brine solution had a molecular weight of less than 120 kDa. Thus, the nutritional composition of oyster mushrooms was significantly influenced by the temperature and period of the canning process. The formation of stable aerated bubbles also demonstrated the efficacy of the brine in preserving the mushrooms despite some nutrient loss.